UPAYA MENINGKATKAN KUALITAS PEROLEHAN SQUALEN PADA MINYAK HATI IKAN HIU DI PERAIRAN CILACAP - Kurniawan, Wahyu; Nurfauzi, Yuhansyah (Sainteks, 2011)
Shark liver oil which becomes the main product for groups of fisherman in Cilacap was produced for traditional food suplement as health product which contains squalen. But the fishermen who processed did not pay attention to the process how to get the shark liver oil stuff so the squalen product could not be guaranted yet as health product. The research aim was to improve the squalen-degree quality of shark liver oil organoleptically.This research was an experimental research. Shark liver oil of bottle-type shark was processed by using a tool which was planned to produce it. The result was analyzed quantitatively to get squalen degree then it was compared to the squalen standard product in the market. The other quality aspects were the physical performance and its organolepty especially of the smell which caused problem. Shark liver oil product of this research was higher than that of standard product in the market and more qualified organoleptically because of the appropriate technology which was applied in its production. The comparison of squalen degree of this research comparing to the standard product in the market is 141 to 191 times bigger. The technology in this research used principle heating of perfect black thing producing more constantly heat in which the heat caused the oil out of shark liver organ. After the oil put into the container in that equipment, the oil was passed or refined using zeolite stone that absorbed substances that were undesirable. Absorbent chemical characteristic of this zeolite stone that would absorb undesirable subtances from the production process of shark liver oil so unpleasant or fishy smell of the oil would be reduced when compared to traditional production processes that relied on more stable direct sun heating without being filtered or refined with zeolite stone. This instrument produced more stable heating process and conditioned the process in the clean room so it could minimaze the contamination from outside. The characteristics of zeolite stone as an absorbent could absorb the undesirable substances like amoniac, so unpleasant smell could be reduced. Keywords: Squalen, shark liver oil, cilacap